2015
DOI: 10.1007/978-3-319-17127-2_8
|View full text |Cite
|
Sign up to set email alerts
|

Attacking Suggest Boxes in Web Applications Over HTTPS Using Side-Channel Stochastic Algorithms

Abstract: Abstract. Web applications are subject to several types of attacks. In particular, side-channel attacks consist in performing a statistical analysis of the web traffic to gain sensitive information about a client. In this paper, we investigate how side-channel leaks can be used on search engines such as Google or Bing to retrieve the client's search query. In contrast to previous works, due to payload randomization and compression, it is not always possible to uniquely map a search query to a web traffic signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Thus to find a string of size n, the attacker needs to send 26 n automated search requests. Later, Schaub et al study how to use stochastic algorithm to deal with variable packet lengths considering that Google has supported variable packet lengths for a given query with payload randomization and Gzip compression since 2012 [58]. For a given length, they create a prefix tree to represent the set of all possible words based on a chosen dictionary and preform hierarchical matching based on the observed size of responded packets.…”
Section: A Related Work: Broader Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus to find a string of size n, the attacker needs to send 26 n automated search requests. Later, Schaub et al study how to use stochastic algorithm to deal with variable packet lengths considering that Google has supported variable packet lengths for a given query with payload randomization and Gzip compression since 2012 [58]. For a given length, they create a prefix tree to represent the set of all possible words based on a chosen dictionary and preform hierarchical matching based on the observed size of responded packets.…”
Section: A Related Work: Broader Discussionmentioning
confidence: 99%
“…Since then, Google has adopted the use of variable-length packets for a given search query with payload randomization and compression. In [58], a stochastic algorithm is adopted to infer the keywords-for a given word length, a prefix tree is created to represent the set of all possible words based on a chosen dictionary and hierarchical matching is conducted based on the observed length of subsequent response packets.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Chen et al [11] showed that financial information, health profiles, and search queries were leaked over HTTPS and WPA by packet inspection. Schaub et al [34] and Sharma et al [35] also presented a black-box tool for side channel weakness quantification using the Fisher criterion. Backes et al [3] adopted a formal approach, enabling information flow analysis to detect side channel attacks.…”
Section: Side Channel Attacks and Defenses On Encrypted Network Trafficmentioning
confidence: 99%